Seller's Responsibility for Non-Conforming Goods in an Online Sale and Purchase Agreement Online at Lazada - Elya Mahmada; Indri Fogar Susilowati (Universitas Negeri Surabaya, 2024)
Buying and selling transaction activities have developed hand in hand with improving technology. The increase in E-Commerce media also gave birth to a Marketplace. One of the Marketplaces in Indonesia is Lazada. In the Civil Code, Article 1457 explains the definition of buying and selling. Even though the agreement was formed with the intention that all transactions go well, when one of the parties does not fulfill the agreement's contents, this is the default. The problem that arises from this is that many sellers commit defaults, such as sending goods that are not suitable. This research aims to find out the form of the seller's default responsibility in the online sale and purchase agreement on the Lazada Marketplace and to find out the buyer's legal protection due to default by the seller in the online sale and purchase agreement on the Lazada Marketplace. This study uses normative legal research. The study results show that sellers committed default cases in carrying out what was promised. However, it should not have been promised. The seller is responsible for exchanging goods in line with the two principles of accountability, namely, the principle of liability based on fault and the principle of breach of warranty. According to Article 1234 of the Civil Code, compensation for costs, losses, and interest due to non-fulfillment of the agreement is only obligatory if the party must fulfill the agreement after being declared negligent in fulfilling the agreement. The seller must carry out the form of responsibility as compensation.